Grazing impacts on ground beetle (Coleoptera: Carabidae) abundance and diversity on semi‐natural grassland - Pozsgai, Gabor; Quinzo‐Ortega, Luis; Littlewood, Nick A. (Insect conservation and diversity, 2022)
Semi‐natural grasslands are commonly managed as a grazing resource for domestic livestock but, due to their unique biodiversity, they are also of conservation interest. Numerous drivers have impacted on the status of these grasslands in recent decades, most importantly changing grazing management strategies. These changes have the potential to affect the biodiversity associated with these habitats, including on some rich invertebrate assemblages. Responses, however, are often dissimilar between different invertebrate taxa. We investigated the responses of ground beetles to different grazing regimes within a replicated, controlled, long‐term grazing experiment on upland semi‐natural grassland in Scotland. Although there was substantial overlap of species composition of ground beetle assemblages in different grazing treatments, species richness, abundance and Shannon diversity of ground beetles were significantly lower in ungrazed plots than in plots subject to high‐ or low‐intensity sheep grazing. Ground beetle abundance (but not species richness or diversity) was lower in ungrazed plots compared to those with low‐intensity mixed grazing by sheep and cattle. However, no differences were identified in abundance, species richness or diversity between the three grazed treatments. Our results suggest that ground beetles may show different responses to grazing compared to responses of some other invertebrate groups and demonstrate the difficulty of attempting to manage grazing to optimise conditions for a wide range of invertebrates. Impacts of grazing management on upland grassland ground beetles were assessed in a fully randomised large‐scale experiment in Scotland. Carabidae diversities negatively responded to decreased grazing pressure but mixed‐species grazing did not increase ground beetle diversity. There was little effect on carabid assemblages, generalist species were dominating. The unclear trends suggest than optimising grazing for multi‐taxon diversity can be difficult in upland grasslands.